Effect of broken roof tile adsorbent in constructed wetland for treatment of laundry waste pollutants - Edward Lie; Haryati Bawole Sutanto; Dhira Satwika (Universitas Gadjah Mada, 2025)
A Constructed Wetland (CW) is a modified wastewater treatment system that can be applied anywhere. The advantages of CW systems are low operational costs, naturally available constituent materials and provide aesthetic value as a wastewater treatment solution. The increasing number of laundry industries causes high concentrations of phosphate pollution in the environment. Shards of tile as an adsorbent may reduce the concentration of Total Suspended Solid (TSS), Total Dissolved Solid (TDS), Chemical Oxygen Demand (COD), phosphate, Methylene Blue Active Surfactant (MBAS), and sulphate. The effect of adding tile fragments is supported by using Water Jasmine plants (Echinodorus palaefolius) and the diversity of microorganisms attached to the adsorbent. The results of this study showed a phosphate reduction efficiency of 99.96%. The presence of the bacterial genus Proteus sp. and Citrobacter sp. on the tile fragments adsorbent impacts phosphate reduction. Pollutant removal in CW systems occurs due to adsorption, sedimentation, filtration, biodegradation and precipitation.